Cutting Edge: Protein Arginine Deiminase 2 and 4 Regulate NLRP3 Inflammasome-Dependent IL-1β Maturation and ASC Speck Formation in Macrophages - Mishra, Neha; Schwerdtner, Lidja; Sams, Kelly; Mondal, Santanu; Ahmad, Fareed; Schmidt, Reinhold E.; Coonrod, Scott A.; Thompson, Paul R.; Lerch, Markus M.; Bossaller, Lukas Friedrich Magnus (The journal of immunology, 2019)
Protein arginine deiminase (PAD) enzymes catalyze the conversion of protein-bound arginine into citrulline, an irreversible posttranslational modification with loss of a positive charge that can influence protein-protein interactions and protein structure. Protein arginine deiminase activity depends on high intracellular calcium concentrations occurring in dying cells. In this study, we demonstrate that protein citrullination is common during pyroptotic cell death in macrophages and that inhibition of PAD enzyme activity by Cl-amidine, a pan-PAD inhibitor, blocks NLRP3 inflammasome assembly and proinflammatory IL-1β release in macrophages. Genetic deficiency of either PAD2 or PAD4 alone in murine macrophages does not impair IL-1β release; however, pharmacological inhibition or small interfering RNA knockdown of PAD2 within PAD4−/− macrophages does. Our results suggest that PAD2 and 4 activity in macrophages is required for optimal inflammasome assembly and IL-1β release, a finding of importance for autoimmune diseases and inflammation.
Prepublished online 10 July 2019
Gesehen am 21.04.2020